Bioassay Guided Isolation of Natural Products - Proceedings of the 10th Annual Seminar and UNESCO Regional Workshop on the Bioassay Guided Isolation of Natural Products Universiti Kebangsaan Malaysia, Bangi 18-23 October 1993 649418; Ikram M. Said, editor 179127; Zuriati Zakaria, editor 179043; Harun Hamzah, editor 649419 (Bangi, Selangor : Universiti Kebangsaan Malaysia, 1994)
Unknown;